2014
DOI: 10.1016/j.neuron.2014.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the Retinogeniculate Synapse by Bouton Clustering

Abstract: Mammalian sensory circuits become refined over development in an activity-dependent manner. Retinal ganglion cell (RGC) axons from each eye first map to their target in the geniculate and then segregate into eye-specific layers by the removal and addition of axon branches. Once segregation is complete, robust functional remodeling continues as the number of afferent inputs to each geniculate neuron decreases from many to a few. It is widely assumed that large-scale axon retraction underlies this later phase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 57 publications
8
106
0
Order By: Relevance
“…These findings are consistent with observations in cat and primate studies of the complexity of mature RGC axon morphology (Fig. 1A), with multiple segments that can branch off the primary axon within the optic tract (Sur & Sherman, 1982; Hamos et al, 1987; Sur et al, 1987; Garraghty et al, 1988; Dhande et al, 2011; Hong et al, 2014), although the arbors may be more restricted in the primate dLGN (Glees & Le Gros Clark, 1941; Lachica & Casagrande, 1988; Michael, 1988; Conley & Fitzpatrick, 1989). In cat, one RGC axon arbor spans the territory of far more postsynaptic neurons than it contacts (Hamos et al, 1987).…”
Section: Retinogeniculate Connectivitysupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are consistent with observations in cat and primate studies of the complexity of mature RGC axon morphology (Fig. 1A), with multiple segments that can branch off the primary axon within the optic tract (Sur & Sherman, 1982; Hamos et al, 1987; Sur et al, 1987; Garraghty et al, 1988; Dhande et al, 2011; Hong et al, 2014), although the arbors may be more restricted in the primate dLGN (Glees & Le Gros Clark, 1941; Lachica & Casagrande, 1988; Michael, 1988; Conley & Fitzpatrick, 1989). In cat, one RGC axon arbor spans the territory of far more postsynaptic neurons than it contacts (Hamos et al, 1987).…”
Section: Retinogeniculate Connectivitysupporting
confidence: 91%
“…1D shows an example of two such close retinogeniculate boutons along one TC neuron dendrite, highlighting that glutamate released from one bouton can diffuse to postsynaptic release sites of the neighboring bouton (Budisantoso et al, 2012). At a developmental phase when boutons are less clustered (Sur et al, 1984; Hong et al, 2014) and glomeruli have not yet formed, retinogeniculate transmission exhibits extensive gluta-mate spillover between neighboring boutons. In fact, glutamate from the bouton of one RGC axon can spill over to the synaptic cleft of a neighboring RGC axon before eye opening (Hauser et al, 2014).…”
Section: Retinogeniculate Synaptic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, an example of synapse refinement in the absence of axon growth was described in the mammalian central nervous system, where imaging of individual axonal arbors of retinal ganglion cells showed that retinogeniculate synapse remodeling can occur without axon retraction. 33 Four decades after John White's seminal work, we have learned a great deal about DD remodeling, which has provided a rich platform to study the temporal cues 4,6,7,9,10,14,17 as well as the cellular mechanisms that underlie this complete inversion of synaptic connectivity. [22][23][24] Our findings have also revealed a novel role of dynamic MTs in regulating synaptic vesicle transport in the absence of neurite growth or pruning.…”
Section: Discussionmentioning
confidence: 99%